New Chairs in a World of Hurt: Using Trauma-Informed Leadership to Guide Communication, Compassion, and Flexibility for Five New Chairs. - Lisa Jellum; Christina Wolfe; Jessica Lindberg; Erin Shufro; Josie Baudier; Jayme Wheeler (Academic Chairpersons Conference Proceedings, 2022)
Presenters will discuss their challenges as first-year Chairs facing the multiple academic fires generated by an unprecedented global pandemic. The presenters will detail how using Trauma-Informed Leadership styles allowed them to adjust for the unpredictability of communication from system-level administration, establish relationships with internal stakeholders, and develop trust with faculty as new leaders within the institution.
Keywords: Academic Leadership; Community College; Faculty; Trauma-Informed